(untitled) (Journal of Oriental Studies, 2019)
Korean literature of the Soviet period was formed in close connection with the historical and social development of society. It was influenced by all socio-political events: from the first five-year plans to perestroika. The literature of that period and subsequent years was quite ideological. Only in the late 1980s koryosaram writers were able to raise questions of lost identity, language and culture, also they could tell stories from memories of a painful past, express sadness and pain from the loss of their native land, the loss of their native language. The stories of Han Dina “Fear” and “hat is the name of that land ...” are one of the first stories that fully describe the history of the deportation of Koreans and their future life in a new land. The main goal of the research is to study the fate of Koreans after their forced resettlement to Kazakhstan and Central Asia, to consider the main problems next generation of Koreans faced based on the analysis of the stories of Han Din. The following scientific methods were used in the article: biographical, structural, hermeneutic. The theoretical significance of the work lies in the fact that its results can serve as a basis for further research of Khan Din’s, as well as in the study of literature to koryosaram, in particular. The methodological basis of the research are the works of Korean, Kazakhstan and Russian literary scholars on the analysis of the literature of the koryosaram and the works of Han Din, such as Kim G.N, Lee Jong-hee, Kim Philyang, Pak Myung-jin and many others. The results of the analysis of two stories written by Han Din allowed judging the change in the concept of “homeland” in the first and subsequent generations of Koreans, as well as the presence of a large language barrier between several generations of Koreans. Key words: koryosaram literature, deportation, national identity, Far East, homeland, provocateur, generation.